Esports physical exercise/performance matrix 1.0 country factsheets: results and analyses from Serbia - Xuanyu Zhou; Yuwen Hu; Radenko M. Matic; Radenko M. Matic; Stevo Popovic; Stevo Popovic; Stevo Popovic; Stevo Popovic (Frontiers in Public Health)
The Serbian Country Factsheets on Physical Exercise and Performance for Esports Players provide a foundational assessment of nine physical exercise and performance indicators tailored to esports athletes. This study utilizes Serbia’s Esports Physical Exercise/Performance Matrix 1.0 framework, integrating recent peer-reviewed studies and nationally representative secondary data to evaluate these indicators. However, insufficient data was identified, with all indicators scoring zero due to unreliable evidence. This fact highlights a critical need for targeted health initiatives within Serbia’s esports community. Considering the strong correlation between physical fitness and cognitive skills essential for esports success, the findings suggest that prolonged physical inactivity may impair Serbian players’ competitive potential. Serbia risks falling behind in this rapidly evolving field without a coordinated, cross-sectoral approach to health promotion tailored for esports. This factsheet is a pioneering resource for Serbian esports, aiming to stimulate further research, inform policy adjustments, and foster community engagement to build a healthier and more resilient esports population.